Do Emotional Faces Affect Inhibition of Return? An ERP Study - Jia, Liping; Wang, Jingxin; Zhang, Kuo; Ma, Hengfen; Sun, Hong-Jin (Frontiers in Psychology, 2019)
Inhibition of Return (IOR) refers to an individual's slowed localization or discrimination performance for targets that appear in previously cued versus uncued location after a relatively long delay (≥300ms). The current study adopted a cue-target paradigm and used behavioural and event-related potentials (ERPs) measures to investigate whether IOR would be modulated by emotional faces during an emotion recognition task. IOR were found for both fearful face target and neutral face target and comparable IOR was found in reaction time measure for fearful and neutral faces. Valid cues were associated with a smaller P1 and a larger N1 than that for invalid cues. Fearful faces were associated with a larger N170 than neutral faces. The onset latency of the stimulus-locked lateralised readiness potential (LRP) in the valid cue condition was longer than that in the invalid cue condition, while there was no significant difference on the onset latency of the response-locked LRP between the valid cue and invalid cue condition. The results support the notion that the inhibitory bias of attention before response contribute to the IOR.